ProteInOn: A Web Tool for Protein Semantic Similarity - Faria, Daniel (2007)
Bioinformatics arose from the need to manage and extract knowledge from the vast amount of sequence data generated by automated Molecular Biology techniques. One important step for this was the development of the Gene Ontology (GO), which provided a unified and structured vocabulary to describe proteins, and also a background to compare them, contributing to the integration of knowledge from the sequence level to the system level. Several approaches have been proposed to measure protein similarity in this context, but there are few tools for this purpose available to the scientific community. We present a new web tool, ProteInOn, focused on calculating GO-based protein semantic similarity. It features a stepwise query selection menu, which together with the possibility of selecting results as input for new queries, makes it flexible and customizable. It also incorporates data on protein interactions, allowing for comparative studies between protein similarity and interactions. The tool implements a preliminary weighting factor which increases the specificity of existing semantic similarity measures, and a score for measuring the representativeness of a GO term within a set of proteins. ProteInOn is available at: http://xldb.fc.ul.pt/biotools/proteinon/